International Students’ Satisfaction of ISO 9001 Certified Education: A Basis for a Preventive and Corrective Program - Peprah, Williams Kwasi (11th International Scholars Conference, 2018)
The concept of people seeking education outside their country has been with humanity for a very long time. It is all because of the perception of quality education or non-existing schools, programs or courses in the home country. This quantitative study was based on the service quality (SERVQUAL) dimensions of reliability, assurance, tangible, empathy and responsiveness coupled with ISO 9001 requirement of conformity and nonconformity to determine the level satisfaction of international students on an ISO 9001 certified institution in the Philippines and developed a responsive program. Responses from 100 conveniently selected international students in 10 ISO certified universities have been analyzed with SPSS 20. The results indicate that the overall service quality of these universities is moderately satisfied. Again, the SERVQUAL determinants of Assurance, Tangibles, and Empathy are all moderately satisfied to indicate conforming to observation. Reliability indicated conformance with the opportunity to improve. However, Responsiveness is noted to be slightly satisfied which is a minor non-conformity. It requires immediate root-cause analysis and using correction and corrective actions to seek continual improvement. The Preventive and Corrective Program should be based on orientation, training, educating, communication and repair and maintenance and beautification. The paper recommends the universities, CHED and ISO certifying institutions intensify their standards to address the elements of Assurance, Tangibles, Empathy and more importantly, Responsiveness.